Analisis Motivasi Kinerja Karyawan PT. Kelola Mina Laut Gresik - Adawiyah, Robi'atul; Kurniawan, Aries (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the motivational factors that influence employee performance at PT Kelola Mina Laut Gresik. The research method uses a qualitative approach with data collection through interviews. The research sample consisted of 20 respondents who were employees from various company divisions. The analysis results show that intrinsic motivation, such as recognition, responsibility, and opportunities for development, has a significant positive impact on employee performance. Apart from that, extrinsic factors such as financial incentives and work environment also have a strong influence on performance. These findings illustrate the importance of paying attention to aspects of intrinsic and extrinsic motivation in improving employee performance at PT Kelola Mina Laut Gresik. The practical implication of this research is the need for companies to pay attention to the recognition system for achievements, provide appropriate incentives, and create a work environment that supports employee development. This research contributes to company management in designing more effective motivation strategies to improve employee performance, which in turn can have a positive impact on productivity and work quality at PT Kelola Mina Laut Gresik.